2019
DOI: 10.1037/arc0000056
|View full text |Cite
|
Sign up to set email alerts
|

Stereotype threat and women’s work satisfaction: The importance of role models.

Abstract: Globally across OECD countries, increasingly more women than men are graduating from a higher education institution with at least a bachelor's degree (OECD, 2017), yet women continue to be highly underrepresented in top leadership positions around the world. What can explain the stark workplace and economic gender inequity despite the growing pool of educated women? One key contributor to gender inequity in the workplace is the psychological experience of women, and decades of research have found that concerns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 66 publications
2
13
0
Order By: Relevance
“…Our findings about gender and race are consistent with other researchers ( Ellis, 2001 ; Cortland and Kinias, 2019 ). Cortland and Kinias (2019) observed that women in the workforce feel less work satisfaction when they feel less role models, sponsors, or peer support are available.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings about gender and race are consistent with other researchers ( Ellis, 2001 ; Cortland and Kinias, 2019 ). Cortland and Kinias (2019) observed that women in the workforce feel less work satisfaction when they feel less role models, sponsors, or peer support are available.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings about gender and race are consistent with other researchers ( Ellis, 2001 ; Cortland and Kinias, 2019 ). Cortland and Kinias (2019) observed that women in the workforce feel less work satisfaction when they feel less role models, sponsors, or peer support are available. Ellis investigated the experiences of black and white doctoral students at a predominantly white research institution to determine whether there were differences in student socialization, satisfaction with doctoral study, and commitment to degree completion based on race or gender.…”
Section: Discussionsupporting
confidence: 93%
“…Our participant pools only represented women and men who understood English, were reachable through online platforms in India, and whose self-reported demographic characteristics revealed that they were well-educated on average. A natural extension would be to conduct experiments involving more or less vulnerable consumers with varying levels of literacy, connectivity, or stable sources of psychological resilience (e.g., self-compassion or positive role models; Cortland & Kinias, 2019; Wollast et al, 2019).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Reducing fears related to stereotypes at work, especially in women holding managerial positions, has a huge impact on their job satisfaction and reduces their fears. Various authors point to the importance of social support in equalizing opportunities for women and reducing gender inequalities in workplaces [20].…”
Section: Women's Psychological Problems In Connection With the Decision To Breastfeedmentioning
confidence: 99%